Training students to develop creative and innovative talents - Hawlader, Mohammad Nurul Alam (2011)
Creativity is the ability of a person that enables him/her to think of, dream up or visualize unusual solution to a problem. It plays an important part in the development of a nation. Generally, a creative process involves five significant steps: first insight, preparation, incubation, illumination and verification. Innovation, on the other hand, is the process of reducing creative ideas to practice, making some systems, components or equipment. The success of a creative process depends to a great extent on the individual, and the environment that exists around him / her. The generation of ideas is considered one of the most important elements, where brain-storming plays an important role, which is subjected to stringent evaluation process before being implemented. An encouragement and support from educators towards creative signs of students would help in the development of creativity. An awareness of creative and innovative process and an involvement in the solution of a creative problem may help students to develop creative and innovative talents. To promote creativity and innovation, areas e.g. projects, laboratory experiments, design of systems and components, where opportunities exist for the development of creativity, should be identified to play an active role in it.